Silencing circOMA1 Inhibits Osteosarcoma Progression by Sponging miR-1294 to Regulate c-Myc Expression - Shi, Yubo; Tian, Yunyun; Sun, Xiangran; Qiu, Yonglong; Zhao, Yingchun (Frontiers in Oncology, 2022)
Background: Several studies have reported that circRNAs have a crucial function in the tumorigenesis of various cancers. However, the expression and function of circOMA1 in osteosarcoma is unknown. Methods: circOMA1 was identified through bioinformatics analysis. qRT-PCR was used to assess the expressions of circOMA1, miR-1294, and c-Myc in osteosarcoma tissues. Further, we performed functional experiments to explore the biological function of circOMA1 in osteosarcoma. Moreover, a luciferase reporter assay, RNA immunoprecipitation (RIP), and fluorescence in situ hybridisation (FISH) assay were performed to demonstrate the association between circOMA1 and miR-1294. Results: circOMA1 exhibited considerable upregulation in osteosarcoma tissues compared with adjacent normal tissues. Silencing circOMA1 suppressed osteosarcoma progression in vitro and in vivo. Mechanically, circOMA1 functioned as a sponge of miR-1294 to upregulate c-Myc expression. Conclusion: circOMA1 played the role of an oncogene in osteosarcoma and promoted osteosarcoma progression by mediating the miR-1294/c-Myc pathway, which might be a new target for treating osteosarcoma.